Comparative study of surrogacy related laws in UK, USA and India - Aslam, Mohammad; Singh, Uday Veer (Journal of Neonatal Surgery, 2025)
In the global critique and public discussion of commercial surrogacy, income inequality has emerged as a central theme. We examine surrogacy from a gender perspective using available empirical data, including our two field studies in India and the US, and demonstrate how the visibility of gender inequities in a transnational environment promotes presumptions at the local and national levels. By doing this, we draw attention to the story of inequity, examine the complexities of surrogacy beyond a single narrative, and demonstrate how that story works to obscure the nuanced, lived realities of people who participate in surrogacy